Planificación del Sistema de Inventarios. Caso de Estudio Photoclub Flash, División Comercial Hicacos - Yasniel Sánchez-Suárez; Leydis Trujillo García; Maylín Marqués-León; PANCORBO SANDOVAL, JOSÉ ARMANDO (Universidad UTE, 2023)
The objective of this article is to plan the inventory system at Photoclub Flash, Commercial Division Hicacos, Varadero. The methods and techniques used are the bibliographic review, direct observation and brainstorming; in addition, methodologies resulting from the work of the national and international scientific community are used, such as the application of the ABC Method, supported by computer tools such as Microsoft Office Excel, EndNote X7 and the FC and ITS modules of WinQSB, which provide a scientific basis for the research. Among the main results include inventory planning, a description and representation of the process, prioritization of products (main product, cartons, etc.), and the products are prioritized (main product ink cartridge), the demand for ink cartridge (2 129.5 ml) is forecast and the company's order lead time is reduced to two days. Therefore, it can be concluded that the ink cartridge is one of the most important products for the company, since it is the most demanded product for the realization of the photographic process. Adequate planning of its inventory would require ordering every 13 days, with a total cost of maintaining units in inventory of 42.90 cuban pesos and purchase equivalent to 1 192.52 cuban pesos.
Keywords: Inventory planning; Inventory systems; Logistics management.